Representation of Symbolic Violence in Women's Body In Online Media (Case Study at Tribunnews in Covering the Case of Online Prostitution by Artist Vanessa Angel) - Algooth Putranto; Santi Delliana (Kanal: Jurnal Ilmu Komunikasi, 2019)
The research aims to explain the form of symbolic violence against a woman as a victim of online prostitution crime in the online news framing. It took an example of news on the victim of online prostitution crime Vanessa Angle case on Tribunnews published during January 2019. There are three findings from the research include news frames of the victim of online prostitution crime victims, 3 form of symbolic violence and the factors affecting the process of news framing. The result of data analyses found two of news frame, in the form of (a) economic frame (b) law and morality frame. The realization of symbolic violence contained in both of frames, include: (a) gender bias of affecting the framing process by Tribunnews found in this research are: (a) patriarchy and misogyny ideologies (b) benefit of business interest and (c) vision and mission of editorial.